Infection-Induced Resistance to Experimental Cerebral Malaria Is Dependent Upon Secreted Antibody-Mediated Inhibition of Pathogenic CD8+ T Cell Responses - Shaw, Tovah N.; Inkson, Colette A.; Villegas-Mendez, Ana; Pattinson, David J.; Strangward, Patrick; Else, Kathryn J.; Draper, Simon J.; Zeef, Leo A. H.; Couper, Kevin N. (Frontiers in Immunology, 2019)
Cerebral malaria (CM) is one of the most severe complications of Plasmodium falciparum infection. There is evidence that repeated parasite exposure promotes resistance against CM. However, the immunological basis of this infection-induced resistance remains poorly understood. Here, utilising the Plasmodium berghei ANKA (PbA) model of experimental cerebral malaria (ECM), we show that three rounds of infection and drug-cure protects against the development of ECM during a subsequent fourth (4X) infection. Exposure-induced resistance was associated with specific suppression of CD8+ T cell activation and CTL-related pathways, which corresponded with the development of heterogeneous atypical B cell populations as well as the gradual infection-induced generation and maintenance of high levels of anti-parasite IgG. Mechanistically, transfer of high-titre anti-parasite IgG did not protect 1X infected mice against ECM and depletion of atypical and regulatory B cells during 4X infection failed to abrogate infection-induced resistance to ECM. However, IgMi mice that were unable to produce secreted antibody, or undergo class switching, during the repeated rounds of infection failed to develop resistance against ECM. The failure of infection-induced protection in IgMi mice was associated with impaired development of atypical B cell populations and the inability to suppress pathogenic CD8+ T cell responses. Our results, therefore, suggest the importance of anti-parasite antibody responses, gradually acquired and maintained through repeated Plasmodium infections, for modulating the B cell compartment and eventually suppressing memory CD8+ T cell reactivation to establish infection-induced resistance to ECM.